Alzheimer's disease and other neurodegenerative dementias in comorbidity: A clinical and neuropathological overview - Matej, Radoslav; Tesar, Adam; Rusina, Robert (Clinical biochemistry, 2019)
Neuropathological diagnostic criteria of neurodegenerative disorders are based on the presence of specific inclusions in a specific area of brain tissue that correlate with clinical manifestations. Concomitant neurodegenerative disorders correspond to a combination of two (or more) different fully developed diseases in the same patient. Concomitant neurodegenerative pathology represents the presence of definite neurodegeneration and deposits of pathological proteins specific for another disease, which is not, however, fully developed. Very frequent overlaps include Alzheimer's disease and alpha-synuclein inclusions. Nevertheless, careful neuropathological investigations reveal an increasing frequency of different co-pathologies in examined brains. In Alzheimer's disease, protein TDP-43 may co-aggregate, but it is not clear whether this is atypical isolated Alzheimer's disease or overlap of Alzheimer's disease with early frontotemporal lobar degeneration. Comorbidities of Alzheimer's disease and tauopathies are relatively rare. A combination of vascular pathology with primary neurodegeneration (mostly Alzheimer's disease or dementia with Lewy bodies) is historically called mixed dementia. Overlap of different neuropathologically confirmed neurodegenerations could lead to atypical and unusual clinical presentations and may be responsible for faster disease progression. Several CSF biomarkers have been evaluated for their utility in diagnostic processes in different neurodegenerative dementias; however, evidence regarding their role in neurodegenerative overlaps is still limited.
Keywords: DNA-Binding Proteins; alpha-Synuclein; Humans; TDP-43; Mixed dementia; DNA vazebné proteiny; demence s Lewyho tělísky; Protein Aggregation, Pathological; Lewy Body Disease; tau Proteins; lidé; Alzheimer Disease; Biomarkers; Alzheimerova nemoc; proteiny tau; Synucleinopathy; Neurodegeneration; biologické markery; patologická konformace proteinů; alfa-synuklein; Alzheimer's disease; Tauopathy